The Effect of Financial Literacy on Investment Decision Making in Southern Lebanon - Alaaraj, Hassan; Bakri, Ahmed (International Business and Accounting Research Journal, 2020)
This study examines the effect of financial Literacy on investment decision making among investors in South Lebanon. Financial literacy is expressed in terms of knowledge and awareness while investors’ decision-making is described as the act of investors and the way they interpret, anticipate, investigate, and assess the steps and transaction for decision making. This includes investment risk, investment decision model and process. To achieve the research objective, a quantitative approach was applied in which 150 self-administered questionnaires were collected using convenience sampling. The sample includes customers of four different Banks in South Lebanon. The data was analyzed using SPSS software. Descriptive statistics were identified and proposed hypotheses were tested using Pearson correlation and multi-regression analysis. Results showed a positive significant relationship between financial literacy and investment decision making. Future studies are encouraged to expand the research to other regions in Lebanon over a longer time horizon in addition to applying other variables.